Chemoradiation therapy changes oral microbiome and metabolomic profiles in patients with oral cavity cancer and oropharyngeal cancer. Issue 5 (2nd February 2021) - Lim, Yenkai; Tang, Kai Dun; Karpe, Avinash V.; Beale, David J.; Totsika, Makrina; Kenny, Liz; Morrison, Mark; Punyadeera, Chamindie
Abstract: Background: Patients with oral cavity cancer (OCC) and oropharyngeal cancer (OPC) are often seen with locoregionally advanced disease requiring complex multimodality treatments. These treatments may have detrimental effects on the oral microbiome, which is critical to maintaining physiological balance and health. Methods: The effects of different OCC and OPC treatment types on the oral microbiome and metabolomic profiles for 24‐month post‐treatment in patients with OCC and OPC were investigated using 16S rRNA gene amplicon next‐generation sequencing and gas chromatography–mass spectrometry (GC–MS), respectively. Results: Chemoradiation resulted in oral dysbiosis with specific depletion of genera which regulate the enterosalivary nitrate–nitrite–nitric oxide pathway. These data also correlate with the oral metabolomic profiles with nitric oxide‐related precursor, modulator, or catalyst significantly downregulated in saliva samples from patients' postchemoradiation. Conclusions: Together, we have shown that oral dysbiosis due to the effects of chemoradiation could potentially have an impact on OCC and OPC patient's quality of life post‐treatment. Abstract : Chemoradiation therapy changes oral microbiome and metabolomic profiles in oral cavity cancer and oropharyngeal cancer patients.